Efektivitas Pelaksanaan Program Hukum dan Rancangan UU dalam Bidang Hukum dan Perundang-Undangan di DPRD Ponorogo - Aghnia Salma Salsabila; Edi Santoso (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to analyze the effectiveness of the implementation of legal programs and draft laws carried out by the Law and Legislation sub-section in the Ponorogo DPRD. Legislation is a written law that is formed through authorized officials and authorized parties and is realized in written form that must be obeyed by the community. In law and legislation there is a norm that serves as a guide for the community to carry out life and behavior within the state. In government institutions, especially DPRD has a sub-section which is tasked with managing legislation and implementing a regulatory system according to the guidelines in every government activity and activity. The legal and statutory department in the DPRD has the task of carrying out the implementation of laws and regulations as well as researching the formulation of laws and regulations by conducting legal studies and providing legal assistance to parties in need supported by publishing and documenting legal products within the institution.